Correction of maternal serum bile acid profile during ursodeoxycholic acid therapy in cholestasis of pregnancy - Brites, Dora (2017)
Background/Aims: Intrahepatic cholestasis of pregnancy is characterized by pruritus and increased levels of serum bile acids, and is often associated with premature delivery, fetal distress, and perinatal mortality. The aims of the present study were: (i) to better define the serum bile acid profile in intrahepatic cholestasis of pregnancy and its potential usefulness for differential diagnosis; (ii) to investigate the effect of ursodeoxycholic acid treatment on the bile acid pool; and (iii) to investigate possible adverse effects of therapy. Methods: Fifteen patients with intrahepatic cholestasis of pregnancy were enrolled in this study. Ursodeoxycholic acid (14 mg/kg body weight per day) was administered for 13±5 days. Twenty normal pregnant women served as controls. Serum bile acid profile was analyzed by high-performance liquid chromatography. Results: Patients with cholestasis of pregnancy showed significant alterations in the proportion of primary bile acids, with an increase in cholic acid (64.0±3.0% vs. 32.2±1.8%, p<0.01), and a decrease in chenodeoxycholic acid (20.8±1.4% vs. 31.9±1.3%, p<0.01), as compared to controls, resulting in a marked elevation in the cholic/chenodeoxycholic acid ratio (3.4±0.5 vs. 1.1±0.1, p<0.01). The glycine/taurine ratio was reduced in cholestasis of pregnancy (0.8±0.1 vs. 1.4±0.1, p<0.01). During ursodeoxycholic acid administration its proportion in serum increased from 1.4±0.6% (0.6±0.2 μmol/l) at baseline to 24.7±2.3% (5.9±1.9 μmol/l) with therapy (p<0.01). This increment was accompanied by a significant decrease in the percentage of cholic acid (28.2±2.6%, p<0.01) and an elevation in chenodeoxycholic acid proportion (25.0±1.9%, N.S.). Although lithocholic acid concentration in serum was maintained with treatment (1.2±0.2 μmol/l vs. 1.7±0.5 μmol/l), there was a significant increase in lithocholic acid proportion (p<0.01) from 3.3±0.5% at baseline to 7.4±1.3% during therapy. The glycine/taurine ratio of serum bile acid pool returned to normal after ursodeoxycholic acid administration (1.7±0.3). Conclusions: These results establish the importance of ursodeoxycholic acid treatment for the correction of maternal serum bile acid profile in cholestasis of pregnancy, indicating that ursodeoxycholic acid may improve fetal prognosis.